Effect of a Teacher Autonomy Supportive Social Emotional learning (TAS-SEL) Intervention on Adolescents’ Mental Health - Deli, Wu; Hashim, Rosna Awang; Kaur, Amrita (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this article is to investigate the effect of teacher autonomy supportive social emotional learning (TAS-SEL) program and a regular social emotional learning (SEL) program based on Strong Kids’ curriculum for rural junior high boarding school for knowledge, learning anxiety and dropout intention. The quasi- experiment research design was selected in order to compare the intervention effect among three groups on participants’ Strong Kids knowledge, learning anxiety and dropout intention, including TASSEL intervention group, SEL intervention group, control group, each group had fifty-one participants. The Strong Kids knowledge test and learning anxiety and dropout intention were administered to evaluate the SEL knowledge, students’ learning anxiety and students’ dropout intention before and after the program. Each program was a twelve-session program, each lesson lasted 45 minutes. The findings of the study show that TASSEL and SEL intervention improve the Strong Kids knowledge and reduce learning anxiety, but only TASSEL intervention reduce dropout intention, which demonstrated the importance of teacher autonomy support in delivering SEL intervention on reducing dropout intention. It was concluded that the TASSEL intervention program can be delivered in an educational setting with minimal professional training and resources, while the positive outcome can be observed in a short period of time. Additionally, supportive teaching is effective tool to reduce the dropout intention when combined with SEL intervention whereas, learning anxiety has no direct linkage with dropout intention.